2010
DOI: 10.1016/j.jtcvs.2009.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular failure secondary to chronic overload in congenital heart disease: An experimental model for therapeutic innovation

Abstract: Various aspects of early right ventricular remodeling were analyzed in this model. This model reproduced evolving right ventricular alterations secondary to chronic volumetric and barometric overload, as observed in repaired tetralogy of Fallot with usual sequelae, and can be used for therapeutic innovation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 25 publications
4
38
1
Order By: Relevance
“…This is in line with reports that the chronically volume-overloaded RV cannot increase contractility in response to acute pressure overload (46). Studies in large animal models of combined volume and pressure overload have shown that during disease progression contractility initially increases, but falls back to pseudonormal levels in a more advanced stage of RV dysfunction (28,40,41). Causal factors for the blunted contractility response may include loss of peristaltic contraction pattern (33), disturbed calcium homeostasis (8,26), and changes in coronary perfusion (46).…”
Section: Additional Volume Overload In Ph Blunts the Contractility Resupporting
confidence: 86%
“…This is in line with reports that the chronically volume-overloaded RV cannot increase contractility in response to acute pressure overload (46). Studies in large animal models of combined volume and pressure overload have shown that during disease progression contractility initially increases, but falls back to pseudonormal levels in a more advanced stage of RV dysfunction (28,40,41). Causal factors for the blunted contractility response may include loss of peristaltic contraction pattern (33), disturbed calcium homeostasis (8,26), and changes in coronary perfusion (46).…”
Section: Additional Volume Overload In Ph Blunts the Contractility Resupporting
confidence: 86%
“…However, similar discrepancies were found in animal models of rTOF. An APD prolongation was found in isolated RV myocytes from a similar rTOF pig model22 whereas a recent study in a dog model noted the absence of APD change in the endocardium 23. Our results suggest these discrepancies are likely related to regional APD variations in rTOF RVs.…”
Section: Discussioncontrasting
confidence: 49%
“…Other groups have used the pig for studying PR [18][19][20]. Our porcine model was the first pure model, free of scar tissue, which was examined with morphometric methods and electrophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the hearts were not examined pathologically like in the present study. Nevertheless, Lambert et al also made a porcine 4 months PR model using the surgical methods of Zeltser et al [18]. They examined RV histology and cellular electrical properties.…”
Section: Discussionmentioning
confidence: 99%